Um estudo fenomenológico sobre o sentido do plantão psicoeducativo - Andrade, Renata Capeli Silva (2013)
This study refers to a doctoral research intervention on psychoeducational practice for educators, developed in educational institutions and called psychoeducational Duty. The study objectives were to understand the revealed meaning of psychoeducational Duty to educators and the institutions managers participants and investigate the way how the psychoeducational Duty was shown as a practice of psychoeducational attention for educators. We found that many studies point to the need to develop studies that show the relationship of this with his professional work, and the impact on their personal lives. In research method assume an existential phenomenological orientation, following as reference intakes of Arendt about meaning and narrative. The word "teacher" is not just a concept, because being an educator reveals a person in its entirety, since it can be said that the existence of the educator is formed by the intersections between the personal and professional relationships by establishing, as an existential plot. The sense revealed in the study points to the value of that space both by educators as the heads of the institutions where it happened, because it is seen as a rare moment in which teachers, who seek, can be heard and consider other perspectives to the difficulties faced . It is also shown as a place of understanding that allows the resumption of his own place in the world, and narrative, co-authoring the unique history of each educator and history of the institution. From what proved to emphasize that this practice can indeed contribute to educators in their work, to be able to strengthen these professionals to consider them as subjects of attention and care. This practice, according to the participant was relevant to the health and development of the work